2005
DOI: 10.1021/es048264z
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of Antibiotics on Soil Surfaces:  Laboratory Studies on Sulfadiazine in an Ozone-Controlled Environment

Abstract: Among the processes affecting transport and degradation of antibiotics released to the environment during application of manure and slurry to agricultural land, photochemical transformations are of particular interest. Drying-out of the top soil layer under field conditions enables sorption of surface-applied antibiotics to soil dust, thus facilitating direct, indirect, and sensitized photodegradation at the soil/atmosphere interface. For studying various photochemical transformation processes of sulfadiazine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 32 publications
0
9
2
1
Order By: Relevance
“…The degradation rate constants were 0.0365 and 0.0309 h −1 with the addition of 10 and 50 mg/L of NaNO 3 , respectively. This result is different from those of most previous reports that nitrate mainly promoted the photolysis rate of organic pollutants (Wolters and Steffens 2005;Ji et al 2012;Niu et al 2013). In this work, a high amount of acetonitrile was used as solvent in the irradiated solutions.…”
Section: Effects Of Solution Ph and Initial Tcc Concentrationscontrasting
confidence: 87%
“…The degradation rate constants were 0.0365 and 0.0309 h −1 with the addition of 10 and 50 mg/L of NaNO 3 , respectively. This result is different from those of most previous reports that nitrate mainly promoted the photolysis rate of organic pollutants (Wolters and Steffens 2005;Ji et al 2012;Niu et al 2013). In this work, a high amount of acetonitrile was used as solvent in the irradiated solutions.…”
Section: Effects Of Solution Ph and Initial Tcc Concentrationscontrasting
confidence: 87%
“…Generally, most of the organic pollutants could be disintegrated structurally and even completely mineralized under UV irradiation. 31 Our present results, however, showed that despite the removal rate of CAP reaching up to 50%, there was no signicant change in the TOC content. The high removal rate with low degree of mineralization demonstrated that the target anticancer drug was decomposed into smaller organic molecules rather than carbon dioxide, water, or inorganic salts directly.…”
Section: Discussioncontrasting
confidence: 68%
“…The results clearly indicate a fast, not identified transformation process at the soil surface. Other transformation processes like photodegradation have been reported in the literature (Wolters and Steffens, 2005) as well. Under our experimental condition with plots covered by plastic sheets and partially by wood panels just after the application and due to the strong light absorption in manure we consider this process to be negligible.…”
Section: Resultsmentioning
confidence: 89%
“…Besides the acetylated transformation products, other metabolites are known to be formed from SA (Kreuzig and Höltge, 2005; Wolters and Steffens, 2005; Wehrhan, 2006). These were not covered with our analytical method.…”
Section: Resultsmentioning
confidence: 99%